An Empirical Investigation of Outsourcing Implementation In The Indonesian Manufacturing Industry - Siti Aisyah Tri Rahayu; Lukman Hakim; Malik Cahyadin (Muhammadiyah University Press, 2017)
This study aims to identify regulations and analyze the determinants of outsourcing implementation in the Indonesian manufacturing industry using an analyctic hierarchy process (AHP). We examines both the Indonesian Labor Law–Act No. 13/2003 and the Regulation of Minister of Manpower and Transmigration No. 19/2012 on Conditions for Outsourcing the Implementation of Work to Other Companies. The results suggest that business efficiency, human resource development plan, types of outsourcing, wage level and worker incentive, recruitment and training cost, skilled worker and productivity, recruitment process, and government regulation are the priority factors to implement outsourcing in Indonesian manufacturing industries.